Paratexts in English Translations of Chinese Classical Novels in China Review - Hu, Xin (Journal of Theory and Practice of Social Science, 2024)
This paper takes the Chinese classical novels published in the English periodical China Review as the research object and examines the paratexts in the English translations, particularly paying attention to prefaces, annotations, and other peritexts, to explore the functions and roles of these paratexts in the translation process. By studying the paratexts of Chinese classical novels in China Review, we can understand the translation of Chinese classical novels in the 19th century and their dissemination in the Western world, providing references for the translation and dissemination of Chinese literature.